Integration of cellular and molecular endpoints to assess the toxicity of polycyclic aromatic hydrocarbons in HepG2 cell line. (8th September 2017) - Morgado, Patrícia I.; Jose, Sílvia; Wanke, Riccardo; M. Antunes, Alexandra M.; Cardoso, Ana Sofia; Jordao, Luisa
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are persistent pollutants present in the environment with known mutagenic and carcinogenic properties. In the present study the effects of exposure to single or multiple doses of benzo[ a ]anthracene (BaA), pyrene (Pyr), and 3 halogenated derivatives of these compounds (1‐chloropyrene, 1‐bromopyrene [1‐BrPyr], and 7‐chlorobenzo[ a ]anthracene [7‐ClBaA]) were evaluated in a liver‐derived human cell line (HepG2). Cytotoxicity as assessed by the classic 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) and neutral red assays showed a mild toxic effect in response to single or multiple dose exposure for up to 72 h, except for multiple dose exposure to BaA and 7‐ClBaA (1 μM/d for 4 d) and single exposure to 10 μM BaA. Furthermore, selective mitochondrial and lysosomal toxicity was observed for Pyr and BaA series, respectively. To understand the underlying molecular mechanisms responsible for this effect, reactive oxygen species production, mitochondrial membrane depolarization, lysosomal pH, DNA fragmentation, and early and late apoptosis mediators were evaluated after exposure to single doses of the compounds. All compounds were able to trigger oxidative stress after 24 h as measured by catalase activity, and a good correlation was found between mitochondrial membrane depolarization, lysosomal pH increase, and MTT and neutral red assays. Evaluation of cell death mediators showed that caspase‐3/7, but not annexin‐V, pathways were involved in toxicity triggered by the studied compounds. The integration of all results showed that 1‐BrPyr and BaA have a higher toxicity potential. Environ Toxicol Chem 2017;36:3404–3414. © 2017 SETAC